THE NEED TO AMEND ARTICLE 38 OF THE STATUE OF THE INTERNATIONAL COURT OF JUSTICE - Aljahani, Abdelnaser (PEOPLE: International Journal of Social Sciences, 2018)
Article 38 of the Statute of the International Court of Justice (ICJ Statute) was not introduced initially as the primary reference to the sources of international law because the word “a source” was not mentioned at all in the text of this article. Article 38 has mainly been inserted in the Statute of ICJ as a guide that facilitates the work of judges of the court to settle the disputes between states. However, it is recognised now that this article is regarded as an authoritative statement on the sources of international law (Wallace, 1997).This paper argues that Article 38 (1) no longer reflects the actual sources of international law in the twenty-first century. In other words, there are some new and emerging sources of international law that should be included in Article 38 of the ICJ Statute. For example, the resolutions of the Security Council of the United Nations (not listed in Article 38) intervened in most areas of international law and many of such resolutions no longer are political and executive. The Security Council plays now a legislative role and has become a primary source of international law. Also, the judicial decisions of international courts can be considered in the current time as another primary source and not a subsidiary source, as stated in Article 38 (1) of the ICJ Statute. The decisions of the International Criminal Court and the ad hoc tribunals (created by the Security Council) are a good illustration of such source.This paper concludes that the content of Article 38(1) of the ICJ does not correspond with the actual sources of international law in practice and there is a need to amend this article.